ACTIVITIES OF PRIVATE ATTORNEYS IN THE KUBAN REGION IN THE SECOND HALF OF XIX - EARLY XX CENTURIES - O. Matveyev (Гуманитарные и юридические исследования)
The article is devoted to professional and social activities of private attorneys in the Kuban region in the 1870s -early twentieth century. Despite the fact that their work was intended as a temporary measure, the Institute lasted until the end of 1917. The supervision of private attorneys in the Kuban region was carried out Yekaterinodar district court that issued the certiicate or by the Congress of justices of the peace. For misconduct or professional errors, private attorneys were subject to the same liability as attor-neys-at-law, up to the time of trial and exclusion from the number of attorneys. A private attorney received remuneration from their clients in the same way as oficial lawyers, either in accordance with the tax of 1868, or by written agreement. By the examples of activity of a number of lawyers, features and conditions of work of private attorneys in the Kuban region are shown. The quality of the practice of private attorneys was signiicantly inferior to the level of activity of professional attorneys. The irst attorneys were not always legally trained and ill-equipped to conduct the affairs of private individuals. At the same time, one should mention very fruitful public and advocacy by V. I. Lunin, who created free legal advice for workers, contributed to the development of legal culture in the Kuban. Tact and responsibility were characteristic of private Kuban attorneys G. K. Damanik, V. D., Gurevich, V. M. Vladimirov, etc. Private attorneys were not required to have higher legal education to conduct civil cases, but they had to obtain a certii-cate for the business. Criminal defense could lead a private attorney only with higher legal education and experience of at least 2 years. Over time, before taking on the service of a private attorney, they began to gather the necessary information, which feature interesting assessment of the Institute of private attorneys in the Kuban region. For each attorney Ekaterinodar district court had a folder of personal files, which reflected all his legal practice in the region. With the growth of the number of lawyers, the competition between private attorneys increased. Serious misconduct of a private attorney entailed the deprivation of a certiicate for the right to conduct other people's affairs. However, in general, the role of private attorneys in the development of legal consciousness in the region was great.